2002
DOI: 10.1042/bj20020168
|View full text |Cite
|
Sign up to set email alerts
|

Interactions defining the specificity between fungal xylanases and the xylanase-inhibiting protein XIP-I from wheat

Abstract: We previously reported on the xylanase-inhibiting protein I (XIP-I) from wheat [McLauchlan, Garcia-Conesa, Williamson, Roza, Ravestein and Maat (1999), Biochem. J. 338, 441-446]. In the present study, we show that XIP-I inhibits family-10 and -11 fungal xylanases. The K(i) values for fungal xylanases ranged from 3.4 to 610 nM, but bacterial family-10 and -11 xylanases were not inhibited. Unlike many glycosidase inhibitors, XIP-I was not a slow-binding inhibitor of the Aspergillus niger xylanase. Isothermal tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
112
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 43 publications
8
112
3
Order By: Relevance
“…The chosen strategy for mutational analysis of A. niger xylanase took advantage of data available on the A. niger xylanase-XIP-I complex such as (a) kinetics of inhibition, (b) titration curves, (c) isothermal calorimetry data, and also the availability of (d) the three-dimensional structure of A. niger xylanase (Protein Data Bank code 1UKR) and (e) an efficient heterologous system for expression of A. niger xylanase. The inhibition mechanism of XIP-I against family 11 fungal A. niger xylanase has been studied in detail (48). The inhibition is pH-dependent in the range of 4 to 7 as determined by activity assays and titration curves, illustrating the importance of electrostatic interactions in the strength of the interaction.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The chosen strategy for mutational analysis of A. niger xylanase took advantage of data available on the A. niger xylanase-XIP-I complex such as (a) kinetics of inhibition, (b) titration curves, (c) isothermal calorimetry data, and also the availability of (d) the three-dimensional structure of A. niger xylanase (Protein Data Bank code 1UKR) and (e) an efficient heterologous system for expression of A. niger xylanase. The inhibition mechanism of XIP-I against family 11 fungal A. niger xylanase has been studied in detail (48). The inhibition is pH-dependent in the range of 4 to 7 as determined by activity assays and titration curves, illustrating the importance of electrostatic interactions in the strength of the interaction.…”
mentioning
confidence: 99%
“…XIP-I inhibited both family-10 and 11 fungal xylanases apart from the family 10 Aspergillus aculeatus xylanase with K i values ranging from 3.4 to 610 nM, but bacterial family 10 and 11 xylanases were not inhibited (48). We have previously reported the production and characterization of the A. niger xylanase in Pichia pastoris and shown that the recombinant enzyme was similar to the native enzyme and was competitively inhibited by XIP-I with a K i ϭ 350 nM (33,48). The chosen strategy for mutational analysis of A. niger xylanase took advantage of data available on the A. niger xylanase-XIP-I complex such as (a) kinetics of inhibition, (b) titration curves, (c) isothermal calorimetry data, and also the availability of (d) the three-dimensional structure of A. niger xylanase (Protein Data Bank code 1UKR) and (e) an efficient heterologous system for expression of A. niger xylanase.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While TAXI-I inhibition activity seems to be independent of the pH optima of xylanases, TAXI-II inhibition of xylanases with low pH optima is weak or absent [8]. On the other hand, XIP-type inhibitors with molecular masses of 29-32 kDa, inhibit both family 10 as well as family 11 xylanases, as long as they are of fungal origin [9]. Studies on the molecular identification, isolation and characterization of the TAXI-I gene, together with screening of the available wheat EST libraries, showed clear evidence that TAXIs belong to a newly identified class of plant proteins to which a function as plant protective microbial glycoside hydrolase inhibitor can be suggested [10].…”
mentioning
confidence: 99%